Chemical & biological studies on the constituent of indigenous and introduced accessions of basil (ocimum basiliccun) growing in Malaysia - Abduelrahman, Azhari Hamid Nour (2010)
Basil is a widely distributed aromatic plant that is used as a culinary herb worldwide. The essential oil of basil was also shown to posses some interesting biological activities. The plant exists in several chemotypes, with immensely variable composition of the essential oil. Basil grown on limited scale in Malaysia as ornamental plants. Thus the different composition of the essential oils provide a broad basis for the choice of basil oils to use for different food flavours, cosmetics, aroma therapy or future testing of biological activities.